PENGARUH PENGGUNAAN GADGET DAN MEDIA DIGITAL TERHADAP MOTIVASI BELAJAR SISWA SD - Bau, Mario Ferdinan; Meo, Maria Natalia; Modok, Grasella Ferina Nai; Nitti, Novalianti; Mas'ud, Fadil; Dwiputa, Rahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine in depth the influence of gadget use and digital media on the learning motivation of elementary school students. The rapid development of information technology has made gadgets an inseparable part of children’s daily lives. Gadgets are no longer used solely for communication and entertainment but are increasingly utilized as learning tools that offer various interactive features, such as educational videos, learning games, and literacy- and numeracy-based applications. However, excessive and uncontrolled gadget use can lead to negative impacts on students’ learning motivation. These include decreased concentration, disrupted study schedules, a tendency to prefer entertainment content, and reduced interest in academic tasks. Through a descriptive approach and literature review, this study analyzes various empirical findings related to both the positive and negative effects of digital media use. The results indicate that gadgets can be effective tools for enhancing learning motivation when used in a structured, purposeful, and developmentally appropriate manner. Engaging learning content can stimulate curiosity, facilitate understanding.